La ruta del Paititi y la Pampa bajo una mirada artística - Miura Velarde, Elena Hiroko (2024)
Throughout history it has been seen that there is a desire or intention to extract gold and other riches, which is manifested in a way that is harmful to the environment. This is linked to the bad practices that have historically been related to the industrial Revolution. In Peru for more than 30 years we have seen how this problem has historically affected various regions, one of the most affected being the region of Madre de Dios, whose main economic activity is illegal mining. The purpose of the following investigation is the in-depth study of the Paititi and Pampa routes in Madre de Dios, in favor of the fact that the deep understanding of these two citadels will allow us to shed light not only on part of the history of each one but understand the social problems that we currently face. We will see how these two territories conceived in societies from different timeless periods are crossed by the same impetus and eagerness to search for gold. And how over time this territory has been transformed, along with the ways of inhabiting it, and the indifference neglected by the authorities. We will use the information collected to explore the visualization bank of our object of study, La Pampa and Paititi. The understanding and investigation of these phenomena from the visual will allow us to expose the various changing processes on the conception of these two littleknown citadels that are of vital importance to understand the origin of the heritage due to the desire to search for gold that is replicated in the contemporaneity.